Correlation in the Coronal Angle between Knee and Hindfoot Was Observed in Patients with Rheumatoid Arthritis Unless Talocrural Joint Was Destroyed. (23rd October 2017) - Nishitani, Kohei; Ito, Hiromu; Shimozono, Yoshiharu; Furu, Moritoshi; Azukizawa, Masayuki; Hashimoto, Motomu; Tanaka, Masao; Mimori, Tsuneyo; Matsuda, Shuichi
Abstract : The purpose of this study is to investigate the compensatory correlation between knee and hindfoot in patients with rheumatoid arthritis (RA). This cross-sectional study included 218 patients (407 lower extremities). Radiographs of the hindfoot and full-length posteroanterior hip-to-calcaneus standing radiographs were evaluated. The destruction of the hindfoot was evaluated using the Larsen grading system. The coronal angular deformity of the knee and hindfoot was evaluated by the femorotibial angle (FTA) and the angle between the tibial shaft and the entire hindfoot (tibiohindfoot angle, THFA). The correlation between FTA and THFA was determined by Pearson's coefficient. For all patients, FTA correlated to THFA (R = 0.28, p < 0.001 ). The correlation was observed as long as the talocrural joint was preserved (Larsen grade ≤ 2), even if the subtalar joint had been destroyed (Larsen grade ≥ 3). However, the correlation was not observed when the talocrural joint was destroyed (Larsen grade ≥ 3, R = −0.02, p = 0.94 ). The pain in the hindfoot did not correlate with FTA or THFA. In conclusion, a compensatory deformity of the hindfoot against the deformity of the knee was observed in RA, and the correlation was lost when talocrural joint was destroyed.